Trends and Themes in Financial Intermediation Research: A Bibliometric Approach - Indriarti, Resti; Sari, Maya; Waspada, Ika Putera (Journal of Business Management Education (JBME), 2024)
This research was designed to examine research developments and look for research gaps regarding Financial Intermediation through a bibliometric analysis approach using VOS Viewer. The Publish or Perish application is used to retrieve the Google Scholar database in order to fulfill research data. The title of the article is used to guide the search process based on the keyword "Financial Intermediation". The search for publication data used as study material was carried out within the last 20 years, namely in the 2003-2023 period. The research results found that there were 989 relevant publications. The research results show that there are three terms that appear most frequently in connection with research publications regarding Financial Intermediation. The first term, namely the term "intermediation", has appeared 426 times with 120 links, and 508 total link strengths. The second term, namely the term "economic growth", has appeared 73 times with 39 links, and 157 total link strengths. The third term, namely the term “Nigeria”, has appeared 57 times with 29 links, and 117 total link strength. Based on the results of the bibliometric mapping, it is still very possible for research related to Financial Intermediation to be researched further and linked to other terms which currently tend to still have a low level of relevance. It is hoped that the results of this research can inspire and develop themes for related articles in the future